2020
DOI: 10.3390/su12208590
|View full text |Cite
|
Sign up to set email alerts
|

Determining the Relationship between Residential Electricity Consumption and Factors: Case of Seoul

Abstract: This paper aims to determine the relationship between residential electricity consumption and other factors by analyzing the correlation and multiple regression between residential electricity consumption and three variables which are known as the factors affecting residential electricity consumption. We used the electricity consumption, income, number of household members, and age of 25 autonomous districts in Seoul as data for analysis, assuming that the socio-demographic characteristics vary from district t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 14 publications
0
9
0
Order By: Relevance
“…Fundamental cause theory explains that differences in health outcomes arise due to relative differences in access to resources according to the social hierarchy (69,70). (71) found that residences of Seoul's power elites were clustered in the city's southeastern area. Considering the evident health inequality according to the SEP in Korea (72, 73), Seoul's geographical health inequalities seem to appear through the high SEP population's affinity for a better environment sorted by housing price.…”
Section: Discussionmentioning
confidence: 99%
“…Fundamental cause theory explains that differences in health outcomes arise due to relative differences in access to resources according to the social hierarchy (69,70). (71) found that residences of Seoul's power elites were clustered in the city's southeastern area. Considering the evident health inequality according to the SEP in Korea (72, 73), Seoul's geographical health inequalities seem to appear through the high SEP population's affinity for a better environment sorted by housing price.…”
Section: Discussionmentioning
confidence: 99%
“…Several studies were conducted to validate the relationship between income and electricity consumption [8][9][10]. The primary analysis was conducted on the data of HVS 2013 to show the relationship between electricity bills per month and income.…”
Section: Relationship Between Income and Electricity Consumptionmentioning
confidence: 99%
“…Overall, their study depicts the changes in gross, agricultural, industrial and services value additions due to the contribution of energy consumption. In South Korea, Kim (2020) considered the relationship between electricity consumption and other factors; income, number of household members, and age, using correlation and multiple regression. A significant correlation is demonstrated in the study while confirming that only income and the number of household members affecting on electricity consumption.…”
Section: Literature Reviewmentioning
confidence: 99%